2009
DOI: 10.3113/fai.2009.0842
|View full text |Cite
|
Sign up to set email alerts
|

Midfoot Ulcers Treated with Gastrocnemius-Soleus Recession

Abstract: The author believes gastrocnemius-soleus recession as a primary treatment of diabetic midfoot ulcers is a low risk method of promoting ulcer resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 16 publications
1
45
0
Order By: Relevance
“…More recently, other techniques to relieve pressure have gained prominence, including gastrocnemius recession and tenotomy of the flexor digitorum longus, peroneus longus, and tibialis posterior. 20,22,23 Our study seems to demonstrate the impact of this line of research.…”
Section: Discussionsupporting
confidence: 56%
“…More recently, other techniques to relieve pressure have gained prominence, including gastrocnemius recession and tenotomy of the flexor digitorum longus, peroneus longus, and tibialis posterior. 20,22,23 Our study seems to demonstrate the impact of this line of research.…”
Section: Discussionsupporting
confidence: 56%
“…In another study, risk for heel ulcers was 15% at a median 12 months follow‐up that also showed that the highest risk for heel ulcers (47%) was in patients with heel anaesthesia and significant dorsiflexion that was possible after ATL; these conditions therefore imply a contraindication . Other studies report no or only a small risk of heel ulceration from ATL . Risk of transfer ulcers after single metatarsal head resection was 41% in an average 13.1 months in one study , while two other studies did not report any transfer ulcers from this procedure at either 6 or 12 months follow‐up .…”
Section: Surgical Offloading Interventionsmentioning
confidence: 94%
“…One RCT with low risk of bias and several non‐controlled studies show the positive effect of ATL, performed primarily to heal recalcitrant forefoot plantar ulcers, in preventing ulcer recurrence . Relative risk reductions over conservative treatment were 75% and 52% at 7 months and 2 years, respectively .…”
Section: Surgical Offloading Interventionsmentioning
confidence: 98%
“…A gastrocnemius recession may be used as an alternative for relief of forefoot pressure 60 and has also been described as an effective treatment for midfoot ulcers (Fig 11). 60,61 …”
Section: Tal Lengtheningmentioning
confidence: 98%